Perilaku Cyberloafing dan Komitmen Organisasi Pegawai di Rumah Sakit: Analisis Korelasional Spearman Rank - M. Nurul Huda; M. Arwani; Mochammad Malik Ibrahim (KOLONI, 2026)
The development of digital technology has increased the ease of access to information in the workplace, including in the healthcare sector. In addition to providing benefits for task performance, internet use can also lead to cyberloafing behavior, namely the activity of using the internet for personal purposes during work hours. This condition is potentially related to the level of employee commitment to the organization. This study was conducted to evaluate the relationship between cyberloafing activities and the level of organizational commitment among employees at the Bhayangkara Hospital, Pusdik Brimob Watukosek. The approach applied was a quantitative study with a correlation design through cross-sectional observations. A total of 40 employees who met the research criteria were selected as samples using a purposive sampling method. Research information was collected through a questionnaire instrument used to identify cyberloafing tendencies and respondents' levels of organizational commitment. The collected data were then processed using the Spearman Rank correlation test. Research findings showed that the majority of respondents had moderate levels of cyberloafing behavior (75.0%) and organizational commitment (80.0%). The results of statistical tests showed a significance value of 0.000 with a correlation coefficient of 0.569. These values ​​indicate a meaningful relationship between the two variables with a level of relationship included in the moderate category. These findings indicate that the level of cyberloafing experienced by employees is related to their organizational commitment. Therefore, an effective internet usage management strategy, coupled with efforts to strengthen organizational commitment, is needed to support employee performance and service quality.